AUDIOBOOKS AND NEW READING EXPERIENCE - Bektursinova, Gulxumar Joldasbaevna (SCIENCE and SOCIETY, 2026)
This article explores the history of audiobooks, their role in modern education and culture, their impact on the reading process, and new approaches to the way people receive information. The author analyzes the convenience of audiobooks, time efficiency, and their potential to enhance the listener’s thinking abilities. The article also compares the differences, advantages, and disadvantages between traditional reading and audiobook listening. The research results indicate that audiobooks serve as an effective tool for shaping a new reading experience and represent an innovative educational resource that meets the needs of today’s readers and listeners.